Total Chromium Captured by Maize (Zea Mays) Plants is Increased by Phosphate and Iron Supplementation in the Soil. Issue 5 (9th March 2018) - González-Alejandre, Magdalena; González-Cortés, Juan Carlos; Carreón-Abud, Yazmín; Martínez-Trujillo, Miguel
ABSTRACT: In this work, a commercial hybrid maize was used, and the effect of selected mineral nutrients [sulfur (S), phosphorus (P), iron (Fe), and nitrogen (N)] on the chromium (Cr) captured by plants was analysed. Seeds were germinated in vitro, and plants were transferred to pots with soil supplemented with a growth inhibitory Cr concentration and different mineral nutrient combinations. Plants were grown for 13 weeks and irrigated with water. In the harvested plants, total Cr was determined considering the Cr concentration in tissues and the biomass as dry weight. The soil supplemented with phosphorus (P) or Fe improved the total Cr captured by plants by a quarter. Bioconcentration values in plant tissues were similar to those of other plants grown in soil with Cr. This information will be useful either for Cr phytoremediation or to protect commercial maize crops cultivated in Cr contaminated soils.